Guaranteeing the Protection of The Right to Freedom of Thought, Religion and Belief According to Legal Principles and Good Governance - Juliana, Agnes (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
This article explores the guarantee and implementation of the right to freedom of thought, religion, and belief in Indonesia, a right that is recognized as fundamental and non-derogable under international human rights law, including the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR), as well as national constitutional and statutory frameworks. Despite these formal guarantees, numerous challenges persist in the practical realization of this right, particularly for religious minorities, indigenous belief communities, and individuals who do not adhere to state-recognized religions. This study applies a doctrinal legal research method to analyze relevant legal provisions, governance practices, and policy impacts. It highlights the inconsistencies between legal commitments and actual practices—such as the use of blasphemy laws and restrictive regulations on places of worship—that contribute to discrimination and exclusion. The article also assesses the role of good governance principles—including transparency, accountability, responsiveness, and the rule of law—in supporting or undermining the protection of religious freedom. Drawing from comparative examples in Albania, Canada, and Nepal, the article proposes policy and legal reforms necessary to align Indonesia’s governance with its human rights obligations. It concludes that meaningful protection of religious freedom in Indonesia requires not only legal reform, but a broader commitment to inclusive governance, institutional accountability, and public education on pluralism and human rights.